Femoral Nerve Block Intervention in Neck of Femur Fracture (FINOF): a randomised controlled trial. Issue 4 (10th April 2018) - Rowlands, Martin; Walt, Gerrie van de; Bradley, Jim; Mannings, Alexa; Armstrong, Sarah; Bedforth, Nigel; Moppett, Iain K; Sahota, Opinder
Abstract : Objective: Fractured neck of femur is a severely painful condition with significant mortality and morbidity. We investigated whether early and continuous use of femoral nerve block can improve pain on movement and mobility after surgery in older participants with fragility neck of femur fracture. Design: Prospective single-centre, randomised controlled pragmatic trial. Setting: Secondary care, acute National Health Service Trust, UK. Participants: Participants admitted with a history and examination suggesting fractured neck of femur. Intervention: Immediate continuous femoral nerve block via catheter or standard analgesia. Outcome measures: Primary outcome measures were Cumulative Dynamic Pain score and Cumulated Ambulation Score from surgery until day 3 postoperatively. Secondary outcome measures included pain scores at rest, cumulative side effects (nausea and constipation), quality of life (measured by EuroQOL 5 D instrument (EQ-5D) score) at day 3 and day 30, and rehabilitation outcome (measured by mobility score). Results: 141 participants were recruited, with 23 excluded. No significant difference was detected between Cumulative Dynamic Pain Score (standard care (n=56) vs intervention (n=55) 20 (IQR 15–24) vs 20 (15–23), p=0.51) or Cumulated Ambulation Score (standard care vs intervention 6 (5–9) vs 7 (5–10), p=0.76). There were no statistically different differences in secondary outcomes except cumulative pain at rest: 5 (0.5–6.5) in the standard care group and 2 (0–5) in the intervention group (p=0.043). Conclusions: Early application of continuous femoral nerve block compared with standard systemic analgesia did not result in improved dynamic pain score or superior postoperative ambulation. This technique may provide superior pain relief at rest. Continuous femoral nerve block did not delay initial control of pain or mobilisation after surgery. Trial registration number: ISRCTN92946117 ; Pre-results.